Forest therapy concept implementation in the sandy soil heath forest area for potential healthcare enhancements - Johari, Nursyafica Nadia; Othman, Rashidi; Mat Ali, Qurratu Aini; Abu Bakar, Ainaa Eliah (Nova Science Publishers, Inc., 2023)
Forest therapy is also referred to as Shinrin-Yoku and is considered natural therapy. It works by providing natural stimuli that trigger relaxation at the physiological level. This form of therapy is used to improve users' wellness through therapeutic recreational aspects. Heath forest primarily has flat surfaces with sandy soil; added strength is not needed. Individuals can use such landforms for recreational purposes like casual exercise and strolling. Users can move quickly after the implementation of an uncomplicated landform structure. Landform triggers individuals to think of the forest as the eyes perceive the scene. Flat landforms are expected to broaden the vision, and better perceive the natural environment. Forests also provide several health benefits and enhance life quality and well-being. Developing a recreational space comprising sandy soil is expected to improve individuals' health and well-being. Nevertheless, the forest must be handled sustainably to preserve its natural condition. Soil is critical for all life aspects, including recreation. Soil health is directly associated with healthy water, air, animals, and plants that help humans relish their surroundings and remain healthy.